Penerapan nilai-nilai Islam dalam proses pembelajaran Bahasa Indonesia di sekolah dasar: Telaah Pustaka - Fitriani, Fajar Ayu (Maliki Interdisciplinary Journal, 2026)
The assessment of Islamic education in elementary schools is a crucial foundation for shaping the character and morals of human resources. Education is the beginning of the formal education process, integrating science and Islamic religion. The purpose of this study was to determine the extent to which Islamic values ​​and general science are understood in the elementary education curriculum in Indonesia. Our research method employed a literature review approach. Research findings from several sources indicate that although Islamic values ​​have been incorporated into the curriculum, their implementation is highly dependent on teacher competence, school environmental support, and integration between subjects. This study recommends ongoing teacher training and strengthening of an Islamic school culture to maximize the implementation of Islamic values ​​in the elementary education curriculum.